PENGEMBANGAN LEMBAR KEGIATAN SISWA DENGAN PENDEKATAN SAINTIFIK PADA MATERI TURUNAN SMA - Erlinda Rahma Dewi; Lihar Raudina Izzati; Dita Purwinda Anggrella (MEGA: Jurnal Pendidikan Matematika, 2023)
This study aims to produce student activity sheets with a scientific approach to high school derivative materials and to determine the quality of student activity sheets from the aspects of validity, practicality, and effectiveness. This type of research is development research. The development model used is the ADDIE development model which consists of analysis, design, development, implementation, and evaluation. The instrument used in this study was the Student Activity Sheet assessment sheet to measure the validity, the response questionnaire to the use of learning devices to measure practicality, and the learning outcome test questions to measure effectiveness. The results showed that the Student Activity Sheet developed was valid because the results of the assessment met the minimum classification "Good". Assessment of Student Activity Sheet gets an average score of 4.1 with the classification "Very Good". Based on the results of data analysis of teacher response questionnaires and student response questionnaires, the Student Activity Sheet is said to be practical because it meets the minimum classification "Good". The results of the teacher's questionnaire response to the use of the Student Activity Sheet got an average score of 3.25 with the classification "Good" and the student response questionnaire to the use of the Student Activity Sheet got an average score of 3.2 with the classification "good". Student Activity Sheets are said to be effective because the percentage of students' classical completeness reaches 84.62%.